2017
DOI: 10.1103/physrevb.95.104427
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties in T2AlB2 ( T =Fe, Mn, Cr, Co, and Ni) and their alloys

Abstract: The electronic structure and intrinsic magnetic properties of Fe2AlB2-related compounds and their alloys have been investigated using density functional theory. For Fe2AlB2, the crystallographic a axis is the easiest axis, which agrees with experiments. The magnetic ground state of Mn2AlB2 is found to be ferromagnetic in the basal ab plane, but antiferromagnetic along the c axis. All 3d dopings considered decrease the magnetization and Curie temperature in Fe2AlB2. Electron doping with Co or Ni has a stronger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
15
30
0
Order By: Relevance
“…in the ESI †) with the absolute value of at least one MAE greater than 1.0 MJ m À3 . For instance, the MAE of Fe 2 AlB 2 has been evaluated by different groups,21,22,26 and our result of À1.14 MJ m À3 is in good agreement with the experimental measurements of À0.9 MJ m À3 at 50 K by Barua 22 and theoretical calculation À1.34 MJ m À3 by Ke. 26 In the newly predicted compounds, the MAB phase Mn 4 PtB 4 has the largest MAE as 13.498, 11.948 and À1.550 MJ m À3 for K 001-010 , K 001-100 and K 010-100 .…”
supporting
confidence: 89%
See 2 more Smart Citations
“…in the ESI †) with the absolute value of at least one MAE greater than 1.0 MJ m À3 . For instance, the MAE of Fe 2 AlB 2 has been evaluated by different groups,21,22,26 and our result of À1.14 MJ m À3 is in good agreement with the experimental measurements of À0.9 MJ m À3 at 50 K by Barua 22 and theoretical calculation À1.34 MJ m À3 by Ke. 26 In the newly predicted compounds, the MAB phase Mn 4 PtB 4 has the largest MAE as 13.498, 11.948 and À1.550 MJ m À3 for K 001-010 , K 001-100 and K 010-100 .…”
supporting
confidence: 89%
“…Moreover, Fe 2 AlB 2 was found to be a promising magnetocaloric material exhibiting an interesting MCE, 20 with the ordering temperature around 300 K conrmed by experimental 21,22 and theoretical studies. [23][24][25] Ke et al 26 investigated the intrinsic properties of Fe 2 AlB 2 , and found a MAE as large as À1.34 MJ cm À3 , in good agreement with the experiments. 22 Recently, Cr 4 AlB 4 with a novel structure of MAB phase has been synthesized consistent with the theoretical calculations.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…After confirming the stability of magnetic Janus VSSe monolayers at an elevated temperature, we further move to check if the ferromagnetic could survive at room temperature. The Curie temperature T C can be estimated by the mean-field approximation (MFA) and Heisenberg model [24,25].…”
mentioning
confidence: 99%
“…In addition, some inconsistencies between bulk and local probe magnetic measurements in the Al(Fe 1−x Mn x ) 2 B 2 were observed. A later first principle calculation suggested that AlMn 2 B 2 should be an anti-ferromagnetic compound [6]. In a recent powder neutron study, AlMn 2 B 2 is identified as a ceramic AFM compound [7] with Neel temperature around 390 K. A study of lattice parameters variation from room temperature to 1200 K revealed that there is a change in anisotropy nature in a and c lattice parameters around 450 K and a local minimum in b lattice parameters around 400 K [8].…”
Section: Introductionmentioning
confidence: 99%